PRINCIPLES OF INTERNATIONAL LAW AND THEIR ROLE IN CONFLICT RESOLUTION IN KOSOVO AND CRIMEA. Part 2 - Люба, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The second part of the article considers the issue of the contradiction of the realization of the right to self-determination and the principle of territorial integrity of Serbia and Ukraine on the example of Kosovo and Crimea. It presents an analysis of the legitimacy of the will expression of Kosovars and Crimeans and its compliance with the norms of international law. The preconditions and factors of the ethnopolitical conflict are examined and the main problematic issues that caused controversies between the central and local authorities in Kosovo and Crimea are identified. The article emphasizes that the result of the plebiscites in Kosovo (1998) and Crimea (2014) was the declaration of independence, denied by central authorities of Serbia and Ukraine and met with mixed reactions by the international community. The self-proclaimed republics have only external features of statehood and are subject to external administration of other countries. A latent opposition of geopolitical opponents in the international arena is noted, which is to some extent traced through the position on the recognition / non-recognition of Kosovo and Crimea. The article draws attention to the fact that inconsistent interpretations of certain principles of international law promote secession movements in countries where conflicts periodically arise between central and local authorities. The emphasis is placed on the necessity of a clearer definition of the aforementioned international legal norms and obligations undertaken by subjects of international law. The article holds that in order to avoid such situations as in Kosovo or Crimea, to eliminate conflicts related to the possibility of an ambiguous interpretation and application of the principles of international law, an internationally recognized system of more stringent and comprehensive measures should be introduced to cease and prevent threats to the territorial integrity of countries. A strong position of the international community on the abovementioned principles with the history of the liberation movements of these peoples taken into account should become the measure precluding the aggravation of conflict situations related to the aspiration of peoples for self-determination.